New contributions to R-curves and bridging stresses - Applications of weight functions - Fett, Theo (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2012)
Most ceramics show an increase of the crack growth resistance during crack propagation (R-curve behaviour). Reasons for such behaviour are bridging effects between opposite crack surfaces, phase transformations around the tip of a crack, and development of micro-cracking zones. This booklet predominantly deals with the bridging behaviour and the discussion of the observed effects in terms of the fracture mechanics weight function procedure.